Revisión sistemática: electro estimulación superficial en pacientes con disfunción de la ATM (2020)
The temporomandibular joint (atm) is mobilized by four pairs of muscles (masseter, external and internal and temporal pterygoid), which create their movements, when they operate with the bone structures, teeth, articular disc, ligaments, blood vessels and nearby nerves. As the function of any of these components is altered or decreased, this is where the syndrome of pain and temporomandibular dysfunction appears. The present work refers to a systematic review on the use of "superficial electrostimulation in patients with TMJ dysfunction" which aims to search for information in different databases in order to determine the determination of this technique. The population sampled was 110 articles of which only 20, that is, 0,22% fulfilled these requirements, the results showed the use of this technique from the systematic review, electrostimulation is effective in the management of pain and other symptoms. The method was by means of a systematic review. Conclusions: 85% of the articles analyzed use electrostimulation as an alternative method for the treatment of pathologies associated with ATMs. 70% of the articles analyzed consider that the use of electrostimulation is effective for pathologies associated with pain symptoms. intense. 15 %% of articles combine electrostimulation with other non-invasive methods. 15% of the articles not presented in the use of electrostimulation. 10% of the articles validate the use of treatments with triantibiotic paste.